Layer-multiple-scattering method for photonic crystals of nonspherical particles - G. Gantzounis; N. Stefanou (Physical Review B, 2006)
We present an extension of the layer-multiple-scattering method to photonic crystals of nonspherical particles in a homogeneous host medium. The efficiency of the method is demonstrated on a specific example of a crystal of metallic spheroids. We report a thorough analysis of the optical properties of this crystal and discuss aspects of the underlying physics that relate to the nonspherical shape of the particles.